Duplex stainless steel forgings and manufacturing method thereof
Patent Information
- Application Number
- JP2021055199
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-29
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2041-03-29
AI Technical Summary
【0022】 本発明により得られる鍛造材は、十分な耐食性を有し、さらに高強度による軽量化を図れ、さらに鍛造の回数を最小限にできるとともに、鍛造時の寸法精度が優れ研削歩留を低減できることで、コストを最小限に抑制できる。
Smart Images

Figure 0007638127000001 
Figure 0007638127000002 
Figure 0007638127000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a duplex stainless steel forging having good corrosion resistance and excellent formability in hot forging, and a method for producing the same. [Background technology]
[0002] Stainless steel, which has good corrosion resistance, is often used for the materials of manufacturing equipment and storage tanks for food and chemicals to prevent metal contamination of the products. Since food often contains salt, SUS316L, which has good corrosion resistance among stainless steels, is often used.
[0003] Recently, duplex stainless steel has been widely used in place of the commonly used austenitic stainless steel. Duplex stainless steel is a type of stainless steel that contains roughly equal amounts of ferrite and austenite phases, and has the advantages of being corrosion resistant, stronger than other stainless steels and carbon steels, allowing for thinner and lighter materials, and using less expensive nickel. For example, duplex stainless steel has come to be widely used in large structures such as floodgates and dams.
[0004] There are six JIS grades of duplex stainless steel: SUS821L1, SUS323L, SUS329J1, SUS329J3L, SUS329J4L, and SUS327L. Of these, SUS821L1 was developed as a replacement for SUS304, and SUS323L was developed as a replacement for SUS316L, while SUS329J3L, SUS329J4L, and SUS327L are highly corrosion-resistant steels that have corrosion resistance even in harsher environments.
[0005] One method for processing and shaping steel is hot forging, which heats and hammers the material to form it. This method can relatively easily form high-strength steel that is difficult to form using cold forging, and is a superior method for manufacturing large parts compared to rolling methods. In food and pharmaceutical manufacturing facilities, flanges are used to connect pipes, etc. These flanges often have complex shapes, and are often manufactured using hot forging.
[0006] One of the issues with applying hot forging to the processing of duplex stainless steel is the precipitation of sigma phase. Sigma phase is an intermetallic compound in which Cr, Mo, etc. are concentrated in Fe, and precipitates when held at around 800℃ to 900℃ for a certain period of time. Even a few percent of sigma phase precipitates, and in addition to reducing hot ductility and causing large cracks during forging, the toughness and corrosion resistance of the material are also greatly reduced. Hot forging generally requires a longer processing time than hot rolling, and the temperature can easily drop below 900℃ during processing.
[0007] In this case, reheating is required to avoid hot cracks, which significantly reduces manufacturing efficiency. Furthermore, the higher the forging temperature, the softer the material becomes, making it more susceptible to deformation, and the greater the amount of thermal shrinkage that occurs when the material is cooled to room temperature, which reduces dimensional accuracy and results in a larger grinding allowance after processing, which reduces costs and reduces workability. Among the types of duplex stainless steel, SUS329J3L, SUS329J4L, and SUS327L have extremely excellent corrosion resistance, but all of them have the problem of precipitation of the sigma phase when forged at low temperatures below 900°C.
[0008] To address this issue, Patent Document 1 discloses a technology in which heat treatment is performed after forging, and the cooling conditions are optimized (heating to 1000°C or higher, then cooling to 500°C at 5 to 12.5°C / min, and then cooling at 10°C / min or higher) to coarsen the average grain size of the ferrite phase to 50 μm or more, thereby suppressing the precipitation of the sigma phase. Moreover, Patent Document 2 discloses a technique for suppressing the precipitation of sigma phases by minimizing the contents of Si and Mn to 0.005 to 0.1%.
[0009] Another characteristic to consider when selecting a material for flanges is the toughness and corrosion resistance of the welded joint, since flanges are often attached to pipes by girth welding. The N contained in duplex stainless steel precipitates as Cr nitrides when heated and cooled during welding. These nitrides promote the propagation of cracks, thereby reducing toughness, and the precipitation consumes Cr, resulting in a so-called Cr-depleted zone, which reduces corrosion resistance.
[0010] Among the types of duplex stainless steel, SUS323L has the same or higher corrosion resistance as SUS316L, and is a type of steel with almost no precipitation of sigma phase, but the corrosion resistance of SUS323L may fall below that of SUS316L depending on the welding conditions. SUS821L1 also has little precipitation of sigma phase, and is a component system with little deterioration in corrosion resistance of welded parts, but since it is a replacement for SUS304, it is not suitable for this application.
[0011] On the other hand, Patent Document 3 discloses a duplex stainless steel material that exhibits excellent corrosion resistance in environments with high chloride ion concentrations similar to brackish water or seawater and is also highly economical. The alloy components are adjusted to C: 0.001-0.03%, Si: 0.05-1.5%, Mn: 0.1-less than 2.0%, Cr: 20.0-26.0%, Ni: 2.0-7.0%, Mo: 0.5-3.0%, N: 0.10-0.25%, Al: 0.003-0.05%, and the duplex stainless steel contains a trace amount of Nb of 0.005-0.10% and the amounts of [Nb] and [Cr] in the extraction residue are optimized. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Japanese Patent Application Publication No. 9-217149 [Patent Document 2] Japanese Patent Publication No. 11-50199 [Patent Document 3] International Publication No. 2018 / 181990 Summary of the Invention [Problem to be solved by the invention]
[0013] The inventors of the present invention have examined the conventional techniques and found that there are problems to be solved. Patent Document 1 describes an improvement by heat treatment after forging, but does not contribute to avoiding forging cracks caused by sigma phase precipitation during forging, improving the associated deterioration of workability, or improving dimensional accuracy.
[0014] In Patent Document 2, extremely low Si and Mn contents require highly purified raw materials, which entails high costs. SUS323L and SUS821L1 can avoid the problem of sigma phase precipitation, but cannot avoid the problem of corrosion resistance of welded parts.
[0015] The steel of Patent Document 3 overcomes the problem of corrosion resistance of welds and may be able to replace SUS316L flanges in terms of corrosion resistance, but it is not clear whether it overcomes the problem of sigma phase precipitation.
[0016] In the end, no technology has been disclosed that can ensure corrosion resistance at or above that of SUS316L, including welds, at low cost while avoiding the cumbersome forging process and low dimensional accuracy. The present invention aims to review the steel composition and manufacturing conditions of duplex stainless steel forgings, thereby suppressing the precipitation of sigma phases while ensuring corrosion resistance, and improving the dimensional accuracy of forged products. [Means for solving the problem]
[0017] It is generally believed that sigma phases are likely to form in duplex stainless steels with high Cr, Mo, and Ni. Reducing these elements will lower the temperature at which the sigma phase precipitates. The inventors have determined this sigma phase precipitation start temperature, and have found that when it is 900°C or lower, forging can be completed without suffering any adverse effects from the sigma phase during manufacturing. This is because the formation of the sigma phase requires the movement of Mo, which has a relatively slow diffusion rate, but the sigma phase precipitation start temperature T SIGMA If is low, T SIGMA This is because even below this temperature, the degree of supercooling that acts as the driving force for precipitation is low, and therefore it takes a considerably long time for precipitation to occur at low temperatures where the diffusion rate is slow.
[0018] On the other hand, Cr and Mo are important elements for improving the corrosion resistance of steel. Therefore, the inventors have conducted extensive research into the range of components and the manufacturing method that minimizes the deterioration of corrosion resistance and does not substantially affect hot forging of the sigma phase, and have arrived at the present invention.
[0019] Specifically, in addition to the steel's composition, the PREN (Pitting Corrosion Resistance Index) is specified to ensure corrosion resistance, and the composition of the ferrite phase, which is the source of sigma phase precipitation in duplex stainless steel, is measured, and the sigma phase precipitation start temperature is specified to be below 900°C based on the composition range.
[0020] Furthermore, as a manufacturing method, the inventors discovered a method for obtaining the ferrite phase composition by specifying the steel composition and the material heating temperature, which led to the present invention. Based on these findings, the gist of the present invention is as follows.
[0021] [1] Chemical composition, in mass%, C: 0.001 to 0.050%, Si: 0.05 to 0.80%, Mn: 0.10% to 3.00%, Cr: 21.5-26.0%, Ni: 3.0-6.0%, Mo: 0.5-2.5%, N: Contains 0.10 to 0.25% moreover Al: 0-0.05%, Nb: 0-0.15%, Ti: 0 to 0.020%, Ta: 0 to 0.20%, Zr: 0-0.05%, Hf: 0~0.08%, Sn: 0-0.10%, W: 0-1.0%, Co: 0-1.0%, Cu: 0-3.0%, V: 0~0.30%, B: 0~0.0050%, Ca: 0 to 0.0050%, Mg: 0 to 0.0050%, REM: 0~0.050%, Contains one or more of the following: The balance is Fe and impurities. Of the impurities O: 0.006% or less, P: 0.05% or less, S: Limited to 0.0050% or less, The PREN represented by the following formula 1 satisfies 28.0 to 35.0, The austenite content is 30% or more and 70% or less by area. The predicted sigma phase precipitation temperature T is calculated using the components distributed in the ferrite phase and expressed by the following formula 2. SIGMA is 900℃ or less Duplex stainless steel forgings characterized by PREN = Cr + 3.3Mo + 16N (Equation 1) T SIGMA =12Cr α +6Ni α +54Mo α +23Si α -15Mn α +465...(Formula 2) In formula 1, the element symbols indicate the content (mass%) of each element in the duplex stainless steel forging, and in formula 2, the element symbols with α indicate the content (mass%) of each element distributed in the ferrite phase in the duplex stainless steel forging. [2] Furthermore, the chemical composition, in mass%, is Al: 0.003-0.05%, Nb: 0.005-0.15%, Ti: 0.003 to 0.020%, Ta: 0.005 to 0.20%, Zr: 0.001 to 0.05%, Hf: 0.001~0.08%, Sn: 0.005~0.10%, W: 0.01 to 1.0%, Co: 0.01 to 1.0%, Cu: 0.01-3.0%, V: 0.01 to 0.30%, B: 0.0001~0.0050%, Ca: 0.0005 to 0.0050%, Mg: 0.0005~0.0050%, REM: 0.005~0.050%, The duplex stainless steel forging material according to [1], characterized in that it contains one or more of the following: [3] The composition according to the above [1] or [2] is used, and the sigma phase precipitation predicted temperature T SIGMA2 2. The method for producing duplex stainless steel forgings according to claim 1, characterized in that the duplex stainless steel material having a hardness of 890° C. or less is heated to 1150° C. or more and 1350° C. or less, and then hot forged. T SIGMA2 =4Cr+28Ni+55Mo+5Si-6Mn-30N+560...(Formula 3) In formula 3, the element symbols indicate the contents (mass %) of the respective elements in the duplex stainless steel forging material. [4] The method for producing a duplex stainless steel forging according to [3], characterized in that in the hot forging, the final surface temperature of the hot forging of the duplex stainless steel material is less than 900°C. [5] A flange made of the duplex stainless steel forging material according to [1] or [2]. [6] The flange according to [5] is used in food and pharmaceutical manufacturing equipment. [7] A welded structure using the duplex stainless steel forging material according to [1] or [2] above. Effect of the Invention
[0022] The forged material obtained by the present invention has sufficient corrosion resistance, and is lightweight due to its high strength. In addition, the number of forging steps can be minimized. In addition, the excellent dimensional accuracy during forging allows the grinding yield to be reduced, thereby minimizing costs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] [Composition of duplex stainless steel] Hereinafter, the reasons for limiting the composition and structure of the duplex stainless steel forging material constituting the present invention will be described first. In this specification, unless otherwise specified, % for components represents mass %.
[0024] If the C content exceeds 0.050%, Cr carbides are formed during hot rolling, which deteriorates the corrosion resistance. Therefore, the C content should be 0.050% or less, preferably 0.030% or less, and more preferably 0.025% or less. On the other hand, the lower limit is not particularly limited, but is set to 0.001% from the viewpoint of the cost of reducing the C content, and is preferably set to 0.025% or 0.005%.
[0025] For deoxidization, the Si content is preferably 0.05% or more, more preferably 0.10% or more, and even more preferably 0.20% or more. On the other hand, an excessive content of Mn deteriorates toughness and promotes the precipitation of the sigma phase, so it is advisable to keep it at 0.80% or less, preferably at 0.50% or less, and more preferably at 0.40% or less.
[0026] Mn has the effect of increasing the austenite phase and improving toughness, so it is advisable to include 0.10% or more, preferably 0.30% or more, and more preferably 0.50% or more. On the other hand, since Mn is an element that reduces the corrosion resistance of stainless steel, its content should be set to 3.00% or less, preferably 2.00% or less, and more preferably 1.50% or less.
[0027] In order to ensure the basic corrosion resistance of the steel of the present invention, the Cr content should be 21.50% or more, preferably 23.00% or more, and more preferably 23.40% or more. On the other hand, if the Cr content exceeds 26.00%, the precipitation of the sigma phase is promoted, and the TSIGMA and T SIGMA2 In addition, the ferrite phase fraction increases, impairing toughness and the corrosion resistance of the welded part when welding is performed. For this reason, the Cr content should be 26.00% or less, preferably 25.00% or less, and more preferably 24.50% or less.
[0028] Ni stabilizes the austenitic structure and improves corrosion resistance to various acids and toughness, so it is advisable to include 3.0% or more of Ni, preferably 4.0% or more, and more preferably 4.5% or more. On the other hand, Ni promotes the precipitation of the sigma phase and T SIGMA and T SIGMA2 Since Ni increases the temperature and is expensive, the Ni content should be set to 6.0% or less.
[0029] Mo is an element that is very effective in increasing corrosion resistance, and in order to ensure corrosion resistance, it is advisable to include 0.5% or more, preferably 1.0% or more, and more preferably 1.2% or more. On the other hand, Mo is expensive and contributes greatly to the promotion of sigma phase precipitation. SIGMA and T SIGMA2 Since Mo is an element that significantly increases the content of steel, it is desirable to suppress it as much as possible. Therefore, the Mo content should be 2.5% or less, preferably 2.0% or less, more preferably 1.8% or less, and even more preferably 1.6% or less.
[0030] N is a strong austenite-forming element, and is also a very effective element for increasing the strength and corrosion resistance of duplex stainless steel by dissolving in the austenite phase, and is also an element that has a high effect of suppressing the precipitation of the sigma phase, so it is advisable to include 0.10% or more, preferably 0.12% or more, and more preferably 0.15% or more. On the other hand, the solid solubility limit of N increases with the Cr content, so if it is contained in excess of 0.25% in relation to the above Cr content, Cr nitrides will precipitate, impairing toughness and corrosion resistance. Therefore, the N content should be 0.25% or less, preferably 0.22% or less, and more preferably 0.20% or less.
[0031] O (oxygen) is an impurity and an element that impairs the hot workability, toughness, and corrosion resistance of stainless steel, so it is preferable to reduce its content as much as possible. Therefore, the O content should be 0.006% or less. There is no particular lower limit for the O content, but extremely reducing the oxygen content requires very high refining costs, so from the standpoint of economic efficiency, the oxygen content may be 0.001% or more.
[0032] P is an element that is inevitably mixed in from the raw materials, and since it deteriorates hot workability and toughness, it is better to have as little P as possible, preferably 0.05% or less. It is preferably 0.04% or less. There is no particular lower limit for the P content, but reducing P to an extremely low level increases the cost of refining. For this reason, from an economical point of view, it is better to set the lower limit of the P content to 0.01%.
[0033] S is an element that is inevitably mixed in from the raw materials, and since it impairs hot workability, promotes cracking during forging, and also deteriorates toughness and corrosion resistance, the less the better, with the upper limit being set to 0.0050% or less. It is preferably set to 0.0020% or less, and more preferably to 0.0010% or less. There is no particular limit on the S content, but reducing S to an extremely low level increases the cost of refining. For this reason, from an economical point of view, it is preferable to set the lower limit of the S content to 0.0001%.
[0034] The balance is Fe and unavoidable impurities. Inevitable impurities include elements contained in the raw materials and elements unintentionally contained during manufacturing.
[0035] Furthermore, as one embodiment of the present invention, one or more of the following elements may be contained instead of Fe. These elements do not have to be contained, and the range of the content includes 0%, and even if they are not contained, it does not affect the solution of the problem of the present invention.
[0036] Al is an element that has a deoxidizing effect on steel, and may be contained together with Ca and Mg to control the composition of inclusions in the steel. Al may be contained together with Si to reduce oxygen in the steel. Al also has the effect of controlling the composition of inclusions and increasing pitting corrosion resistance, and may be contained at 0.003% or more to ensure this effect. It is preferably 0.005% or more. On the other hand, Al is an element with a relatively large affinity for N, and excessive content of Al produces nitrides of Al, which impairs the toughness of stainless steel. Although the extent of this depends on the N content, if the Al content exceeds 0.05%, the toughness decreases significantly, so the content should be set to 0.05% or less, preferably 0.04% or less, and more preferably 0.03% or less.
[0037] Nb is an element that has a strong affinity with N and acts to further reduce the precipitation rate of chromium nitrides. For this reason, Nb may be contained in an amount of 0.005% or more. It is preferably contained in an amount of 0.010% or more, more preferably 0.020% or more, and even more preferably 0.030% or more. On the other hand, if Nb is contained excessively, a large amount of Nb nitrides will precipitate, impairing toughness, so the Nb content should be 0.15% or less, preferably 0.09% or less, more preferably 0.07% or less, and even more preferably 0.05% or less. Although Nb is an expensive element, the cost of raw materials for melting stainless steel can be reduced by actively utilizing the Nb contained in low-quality scrap. It is preferable to reduce the cost of melting Nb-containing steel by such a method.
[0038] Ti may be contained since it has a very strong affinity with N and forms Ti nitrides in steel. However, Ti is prone to form coarse nitrides, and if contained in excess of 0.020%, Ti nitrides impair toughness, so the Ti content should be 0.020% or less, preferably 0.015% or less, and more preferably 0.010% or less. When Ti is contained, it should be 0.003% or more in order to obtain the effect more reliably, preferably 0.005% or more, and more preferably 0.006% or more.
[0039] Ta is an element that improves corrosion resistance by modifying inclusions, and may be contained. However, if the Ta content exceeds 0.200%, it leads to a decrease in room temperature ductility and toughness, so the Ta content is preferably 0.200% or less, more preferably 0.100% or less. When the effect is to be expressed with a small Ta content, the Ta content is preferably 0.050% or less. When Ta is contained, in order to ensure the effect, the Ta content is preferably 0.005% or more.
[0040] Zr and Hf are elements effective in improving hot workability and cleanliness of steel as well as oxidation resistance. Sn may be contained since it has the effect of improving acid resistance. On the other hand, excessive content of these elements promotes grain boundary fracture due to a decrease in grain boundary strength, so it is necessary to keep Zr at 0.05% or less, Hf at 0.08% or less, and Sn at 0.10% or less. In order to obtain these effects more reliably, it is preferable to contain Zr at 0.001% or more, Hf at 0.001% or more, and Sn at 0.005% or more.
[0041] W, like Mo, is an element that improves the corrosion resistance of stainless steel and may be contained. However, since it is an expensive element, it is best to keep it at 1.00% or less, preferably at 0.70% or less, and more preferably at 0.50% or less. If W is contained, it is best to keep it at 0.01% or more to ensure the effect, preferably at 0.05% or more, and more preferably at 0.10% or more.
[0042] Co is an element effective for increasing the toughness and corrosion resistance of steel, and may be contained. Since Co is an expensive element, it is preferable to contain 1.0% or less of Co. It is preferable to contain 0.7% or less, and more preferably 0.5% or less. When Co is contained, it is preferable to contain 0.01% or more in order to obtain the effect more reliably, and it is preferable to contain 0.03% or more, and more preferably 0.10% or more.
[0043] Cu is an element that additionally enhances the corrosion resistance of stainless steel against acids and has the effect of improving toughness, so it may be contained. If Cu is contained in an amount exceeding 3.0%, the solid solubility will be exceeded during cooling after hot rolling, causing εCu to precipitate and embrittle, so it is advisable to contain 3.00% or less. It is preferable to contain 1.70% or less, and more preferably 1.5% or less. If Cu is contained, it is preferable to contain 0.01% or more, preferably 0.33% or more, and more preferably 0.45% or more.
[0044] V has affinity with N and is an element that acts to reduce the precipitation rate of chromium nitrides. For this reason, it may be contained. However, if it is contained in an amount exceeding 0.30%, a large amount of V nitrides will precipitate, impairing toughness, so the V content should be 0.30% or less, preferably 0.25% or less, and more preferably 0.20% or less. When V is contained, it should be contained at 0.01% or more in order to obtain the effect more reliably, preferably 0.03% or more, and more preferably 0.08% or more.
[0045] B is an element that improves the hot workability of steel. In addition, it is an element that has a very strong affinity with N, and if it is contained in a large amount, nitrides of B will precipitate and impair toughness. For this reason, the content should be 0.0050% or less, preferably 0.0040% or less, and more preferably 0.0030% or less. When B is contained, it is preferable to contain 0.0001% or more in order to obtain the effect more reliably, and it is preferable to contain 0.0005% or more, and more preferably 0.0014% or more.
[0046] Ca and Mg may be added to control the composition of inclusions and to improve pitting corrosion resistance and hot workability.
[0047] On the other hand, since excessive content of either Ca or Mg reduces hot workability and toughness, it is advisable to limit Ca to 0.0050% or less and Mg to 0.0050% or less. Preferably, Ca is limited to 0.0040% or less and Mg is limited to 0.0025% or less, and more preferably, Ca is limited to 0.0035% or less and Mg is limited to 0.0020% or less. When Ca and Mg are contained, they are contained by using a melted raw material together with 0.003% to 0.050% of Al, or the contents are adjusted through deoxidation and desulfurization operations so that the Ca content is 0.0005% or more and the Mg content is 0.0005% or more. It is preferable that Ca is 0.0010% or more and Mg is 0.0010% or more, and more preferably Ca is 0.0015% or more and Mg is 0.0015% or more.
[0048] REM is an element that improves the hot workability of steel, and may be contained for that purpose. However, excessive content reduces hot workability and toughness, so it is recommended that REM be contained in an amount of 0.050% or less. It is preferable that REM be contained in an amount of 0.040% or less, and more preferably 0.030% or less. When REM is contained, it is recommended that REM be contained in an amount of 0.005% or more to ensure the effect. It is preferable that REM be contained in an amount of 0.010% or more, and more preferably 0.020% or more. Here, REM refers to scandium Sc, yttrium Y, and lanthanoid rare earth elements such as lanthanum La and cerium Ce, and the REM content is the sum of the contents of each element belonging to REM.
[0049] [Austenite content: 30% to 70% by area] In general, in duplex stainless steels, it is desirable that the amount of austenite is close to equal to the amount of ferrite. If there is too much ferrite, the toughness decreases and Cr nitrides are more likely to precipitate. On the other hand, if there is too much austenite, it impairs hot workability, promotes cracking during forging, and is more likely to cause stress corrosion cracking. Furthermore, in either case, the composition difference between the ferrite phase and the austenite phase becomes significant, and the corrosion resistance of either phase decreases. Therefore, the amount of austenite should be 30% or more by area and 70% or less by area. Since it is preferable that the amount of austenite and the amount of ferrite are as equal as possible, the amount of austenite should be preferably 35% or more, 40% or more, or 45% or more, and similarly, it should be 65% or less, 60% or less, or 55% or less.
[0050] The amount of austenite is determined by measuring the austenite area ratio using a mirror-polished cross section of the steel material, etching it, observing it with an optical microscope, and analyzing the images. The cross section of the steel material may be any cross section in the thickness direction of the steel material (perpendicular to the steel material surface). In order to avoid the effects of processing, it is desirable to measure near the center of the cross section.
[0051] [28.0≦PREN≦35.0] In the case of duplex stainless steels, taking into consideration the decrease in corrosion resistance caused by precipitation of Cr nitrides when welding, a higher PREN is often secured for duplex stainless steels than for austenitic stainless steels when aiming for the same corrosion resistance. Experiments showed that when the PREN, defined by the following formula 1, which is an index of pitting corrosion resistance, is less than 28.0, the corrosion resistance of the weld heat affected zone in a brackish water environment is lower than that of SUS316L, even if the austenite content of the duplex stainless steel base material is 30-70% by area.
[0052] PREN = Cr + 3.3Mo + 16N (Equation 1) In the formula 1, the element symbols indicate the content (mass %) of each element.
[0053] In addition, if the Cr and Mo contents are excessively increased in order to increase the PREN of the duplex stainless steel base material, the TSIGMA and T SIGMA2 It increases the N content, which not only makes the sigma phase more likely to form, but also increases the alloy cost and leads to the formation of intermetallic compounds. On the other hand, an excessive N content has adverse effects such as a deterioration in toughness.
[0054] For the above reasons, in the present invention, the austenite content is 30-70 area % and the PREN value of the duplex stainless steel base material defined by the above formula (1) is 28.0 to 35.0. The PREN value is preferably 29.0 or more, 30.0 or more, 30.5 or more, or 31.0 or more, and is preferably 34.5 or less, 34.0 or less, 33.5 or less, or 33.0 or less.
[0055] [T SIGMA ≦900℃] In conventional duplex stainless steel, when the surface temperature falls below 900°C due to the time required for forging, the sigma phase, an intermetallic compound, precipitates, significantly reducing hot ductility and toughness, which can lead to material cracking. For this reason, reheating was required when the surface temperature fell below 900°C. However, by optimizing the material's components and suppressing the precipitation of the sigma phase, it was discovered that it is possible to obtain a duplex stainless steel material that does not experience a decrease in properties due to sigma phase precipitation during forging.
[0056] In duplex stainless steel, the sigma phase is produced by the phase transformation of the ferrite phase. In view of the fact that component distribution occurs between the ferrite phase and the austenite phase, the inventors have conducted extensive research and found that the equilibrium precipitation temperature of the sigma phase, T SIGMA It was found that it is possible to derive from the content of components distributed in the ferrite phase, and based on this, it was found that a material capable of suppressing sigma phase precipitation can be obtained.
[0057] Specifically, the composition of the ferrite phase of the duplex stainless steel forging was measured, and the compositional contents of the ferrite phase were substituted into the following formula 2 to obtain the equilibrium precipitation temperature of the sigma phase, T SIGMA It was found that it is best to set this to 900°C or less. SIGMAis the predicted temperature of the equilibrium precipitation temperature of the sigma phase, and Equation 2 is its prediction formula. T SIGMA Since it is predicted that the sigma phase will not precipitate unless the temperature is below T SIGMA If the composition is adjusted so that the temperature is low, the forging time until reheating due to temperature drop can be secured. In addition, when the temperature drops, the diffusion of elements necessary for sigma phase precipitation decreases, so the precipitation rate itself is suppressed. Equation 2 is based on an equation obtained by equilibrium calculation using Thermo-Calc (registered trademark), a thermodynamic calculation software from ThermoCalc, and has been further modified by the inventors' experiments.
[0058] T SIGMA =12Cr α +6Ni α +54Mo α +23Si α -15Mn α +465...(Formula 2) In formula 2, the element symbol followed by α indicates the content (mass%) of each element distributed in the ferrite phase.
[0059] The composition of the ferrite phase can be determined by averaging the numerical data of the high Cr and Mo parts, which are clearly separated from the low Cr and Mo parts corresponding to the ferrite phase and austenite phase, when a line analysis is performed in the thickness direction using an EPMA on a mirror-polished cross section of the steel material. Alternatively, after determining the ferrite phase where Cr and Mo are concentrated, multiple points on the ferrite phase can be analyzed and averaged. As in the case of measuring the austenite content, the cross section of the steel material may be any cross section of the steel material, and it is preferable to measure the central part of the cross section.
[0060] [Method of manufacturing forged material of the present invention] Next, a method for producing the forged material of the present invention will be described. A steel having the above-mentioned composition is melted to produce a steel ingot for forging. The method for melting the steel and the method for producing the steel ingot are not particularly limited. A steel ingot for forging can be produced by an existing conventional method. Above T SIGMAis a predicted temperature determined from the content of elements distributed in the ferrite phase in the forged material (forged steel material). Therefore, the components in the ferrite phase after forging must be predicted. Therefore, the inventors came up with the idea of estimating the content of elements in the ferrite phase in the forged material after forging even at the stage of the steel ingot for forging, and predicting the transition precipitation temperature to the sigma phase, and developed T SIGMA2 found.
[0061] [T SIGMA2 ≦890℃] T SIGMA2 is T SIGMA Unlike the formula above, it is calculated based on the element content of the steel. SIGMA Similarly, T SIGMA2 is the predicted temperature of the equilibrium precipitation temperature of the sigma phase, and Equation 3 is the prediction formula. The inventors have found that it is possible to predict the distribution of components to the ferrite phase and the austenite phase by combining the element contents in the steel and the heating temperature. That is, T SIGMA As in the above, there is no need to measure the content of elements distributed in the ferrite phase in the steel, and if the heating temperature of the heat treatment before hot forging is in the range of 1150 to 1350°C, the equilibrium precipitation temperature of the sigma phase is predicted from the content of elements in the steel. Specifically, the steel composition of the duplex stainless steel forging is measured, and the content of each element is substituted into Equation 3 (if the content of each element is known in advance, it can be determined without measuring the content) to obtain the equilibrium precipitation temperature of the sigma phase, T SIGMA2 This is the calculation of T SIGMA2 is T SIGMA It is an index that can be treated in the same way as T SIGMA2 Since it is predicted that the sigma phase will not precipitate unless the temperature is below T SIGMA2 When T is low, the diffusion of elements necessary for sigma phase precipitation is reduced, and the precipitation rate itself is suppressed. SIGMA As in the above, this formula is based on an equation obtained by equilibrium calculation using the thermodynamic calculation software "Thermo-Calc" (registered trademark) of ThermoCalc Corporation, and has been further modified based on the experiments of the present inventors. T SIGMA2 The upper limit of the actual T SIGMATaking into consideration the variation in temperature, the temperature is set to 890°C, and preferably to 880°C, 870°C, 860°C or 850°C.
[0062] T SIGMA2 =4Cr+28Ni+55Mo+5Si-6Mn-30N+560...(Formula 3) In the formula 3, the element symbols indicate the contents (mass%) of the respective elements in the steel.
[0063] [Material heating temperature: 1150~1350℃] Furthermore, the heating temperature of the material during the manufacture of the forged material is specified to be 1150°C or higher and 1350°C or lower. Increasing the heating temperature not only alleviates the segregation of Cr and Mo in the material, but also has the effect of reducing the distribution of Cr and Mo to the ferrite phase, and as a result, the transformation from the ferrite phase to the sigma phase is suppressed. To achieve this effect, the heating temperature should be higher than 1150°C. It is preferably higher than 1170°C, more preferably higher than 1200°C, and even more preferably 1220°C or higher. On the other hand, if the heating temperature is too high, the furnace will be severely damaged, so it is better to set it to 1350°C or lower. It is preferably 1300°C or lower.
[0064] [Final surface temperature of hot forging: less than 900℃] T SIGMA Or T SIGMA2 If the surface temperature is 900°C or less, there is no need to avoid hot cracking due to the precipitation of sigma phases, even if the surface temperature falls below 900°C, so reheating is unnecessary. This allows the number of reheating cycles to be significantly reduced, greatly improving manufacturability. Furthermore, by forging at a low temperature, deformation during processing due to low strength and deformation due to thermal contraction during cooling can be suppressed, improving dimensional accuracy. As a result, grinding man-hours and grinding losses can be reduced.
[0065] According to the findings of the present inventors, even if the surface temperature is less than 800°C, forging is possible without any problems and the dimensional accuracy can be improved. On the other hand, if the surface temperature is less than 500°C, the hot strength becomes too high and it becomes difficult to process. Therefore, the surface temperature during hot forging is preferably 500°C or higher. EXAMPLES
[0066] The present invention will now be described with reference to examples. Table 1 shows the composition of the duplex stainless steel samples. Steel adjusted to the composition of each sample was melted in an MgO crucible in a 25-75 kg vacuum induction furnace in the laboratory and cast into a square steel ingot with a thickness and width of approximately 100 mm. In Table 1, blanks indicate that the corresponding component was not contained. Approximately 20 kg of hot forging material was processed from the main body of the steel ingot, heated to a temperature of 1250°C and held for 2 hours, and then hammer forged to a thickness of 20 mm to obtain a forged material (single forged material). At that time, the surface temperature dropped to approximately 650°C.
[0067] The evaluation results of the forged materials are shown in Table 2. First, the appearance of the forged materials was observed, and those that had cracks several mm deep, which could not be removed by grinding, were marked with an X, and those that did not had cracks were marked with an O. The thickness of the four corners of the forged materials was also measured, and the maximum difference from the target value of 20 mm was recorded as the dimensional error (mm).
[0068] Next, a sample for microstructural observation was taken from the surface layer of the forged material, the cross section was mirror-polished, and observed using an EPMA. Line analysis was performed over a length of 1 mm at 1 μm pitch in the thickness direction of the observed sample, and the high Cr and Mo content of the two parts, which were divided into high and low Cr and Mo content parts, was determined as the ferrite phase. The numerical data was averaged to determine the composition of the ferrite phase.
[0069] In addition, samples that were judged to be cracked were subjected to solution heat treatment by holding them at 1060°C for 1 hour and then water cooling, and pitting test pieces were taken from 1 mm below the surface of the material. To evaluate corrosion resistance, the solution heat treated samples were placed in a 3.5% NaCl solution at 50°C and the pitting potential was measured in accordance with the method specified in JIS G0577. To evaluate toughness, V-notch test pieces were taken from 1 mm below the surface of the solution heat treated samples in accordance with JIS Z 2202, and a Charpy impact test was performed at a test temperature of -20°C.
[0070] Furthermore, to simulate pipe insertion welding, the following welded specimens were created. After polishing the surface of the material, they were cut into 20mm thick x 50mm x 100mm and 5mm thick x 50mm x 100mm. The 20mm x 100mm surface of the former was in contact with the 50mm x 100mm surface of the latter, and the 50mm x 100mm surface of the former was joined at a right angle to the 5mm x 100mm cut surface of the latter on the same plane. Both sides of the contact part were welded by tungsten arc welding (GTAW) to create a welded joint. The welding conditions were as follows: SUS329J3L welding wire with a diameter of 1.2mm was used, welding current: 200A, arc voltage: 12V, welding speed: 20cm / min, 100%Ar shielding gas flow rate: 15L / min.
[0071] To evaluate the corrosion resistance of the welds, pitting test pieces were taken from the cross section of the material so as to include the entire weld heat-affected zone and weld metal, and the pitting potential was measured in a 3.5% NaCl solution at 50°C in accordance with the method specified in JIS G0577.
[0072] Table 2 shows the results of the ferrite phase composition analysis of each forged material, the austenite phase area ratio, the presence or absence of cracks during forging, dimensional error, the corrosion resistance and toughness evaluation of the base material, and the corrosion resistance evaluation of the welded parts. The forged materials of the present invention did not develop any large cracks, had a dimensional error of 1.0 mm or less, had a pitting potential of 0.3 V vs. SSE or more at 50°C for the base material, a pitting potential of 0.28 V vs. SSE or more at the weld, and had an impact value of 100 J / cm at -20°C. 2 The above results show good characteristics.
[0073] On the other hand, the comparative examples No. 14 and No. 16 have excessive Cr and Mo, respectively, so T SIGMA The temperature exceeded 900°C, which resulted in the precipitation of sigma phase during forging and the formation of cracks. SIGMA2 The same was true for No. 21, whose temperature exceeded 900°C. Nos. 9, 11, 13, 15, and 19 had poor corrosion resistance due to excessive C, excessive Mn, insufficient Cr, insufficient Mo, and insufficient PREN, respectively. No. 17 had poor corrosion resistance due to insufficient N, which caused Cr nitrides to precipitate in the weld. No. 18 had excessive N, which caused Cr nitrides to precipitate, and it had poor toughness and corrosion resistance. Nos. 12 and 20 had poor toughness due to insufficient Ni and excessive ferrite, respectively.
[0074] Next, Table 3 shows the results of comparing forged material that was forged in one go without being reheated in between (single-forged material) and forged material that was reheated in between (additional reheating material). As with the above samples, steel materials No. 5, 7, and 21 were heated to a temperature of 1250°C, held for 2 hours, and then hammer forged to a thickness of 20 mm to produce forging materials. When the temperature reached 900°C, a process of reheating to 1250°C was added twice, and forging was completed at above 900°C to obtain forged materials (reheated added materials). The appearance of the materials was observed, and those that had cracks several mm deep that could not be removed by grinding were marked with ×, and those that did not had cracks were marked with ◯. In addition, the thickness of the four corners of the forged material was measured, and the maximum difference from the target value of 20 mm was taken as the dimensional error (mm).
[0075] Table 3 shows the cracking conditions and dimensional accuracy of the reheated and added material and the single forged material. Items A, C, and E are the same as those in Table 2. When Nos. 5 and 7 were forged once, there were no cracking problems and the dimensional accuracy was good. When No. 21 was forged once, large cracks occurred and the product could not be obtained. All three samples of reheated and added material were forged with a minimum temperature of 900°C, so they could be manufactured without cracking problems, but the dimensional error exceeded 1.0 mm, which resulted in a very large load on the grinding process in the subsequent process.
[0076] Furthermore, Table 4 shows the results of investigating the effect of heating temperature. As with the above samples, forging materials were processed from steel materials No. 5, 7, and 21 in the same manner, and the heating temperature was changed between 1130 and 1320°C. After holding at that temperature for 2 hours, forging was performed by hammer forging to a thickness of 20 mm to obtain forged materials (single-forged materials). At that time, the surface temperature at the completion of forging had dropped to about 600 to 880°C. The materials were heated and held at 1060°C for 1 hour, then water-cooled and subjected to solution heat treatment for evaluation.
[0077] c, h, and k in Table 4 are the same as those in Table 2. As the heating temperature decreases, T sigma However, both are at T sigma It can be seen that no cracks occur when the temperature is below 900°C. The boundary temperature is T sigma2 It varies depending on the difference in T sigma2 If the temperature is originally over 890℃, heating to 1150℃ or higher will sigma never exceeds 900°C.
[0078] [Table 1]
[0079] [Table 2]
[0080] [Table 3]
[0081] [Table 4] [Industrial Applicability]
[0082] The duplex stainless steel forging material obtained by the present invention has excellent manufacturability, since the precipitation of sigma phase during manufacturing is almost completely suppressed, and forging cracks can be prevented without reheating. In addition, the forging temperature can be lowered, which improves dimensional accuracy and reduces grinding yield. In addition, the duplex stainless steel forging material has sufficient corrosion resistance equal to or greater than that of SUS316L, including the welded parts, and is lightweight due to its high strength. Furthermore, the cost required for forging can be minimized, which contributes to significant cost reduction and high efficiency, and is extremely beneficial to the industry and the environment. For example, it is expected to be used as a replacement for the current SUS316L in fran materials used in manufacturing equipment and storage tanks for food and pharmaceuticals.
Claims
1. The chemical composition, in mass%, is C: 0.001-0.050%, Si: 0.05-0.80%, Mn: 0.10% to 3.00%, Cr: 21.5-26.0%, Ni: 3.0 to 6.0%, Mo: 0.5-2.5%, N: 0.10 to 0.25%; moreover Al: 0-0.05%, Nb: 0 to 0.15%, Ti: 0 to 0.020%, Ta: 0 to 0.20%, Zr: 0 to 0.05%, Hf: 0-0.08%, Sn: 0 to 0.10%, W: 0 to 1.0%, Co: 0 to 1.0%, Cu: 0-3.0%, V: 0 to 0.30%, B: 0 to 0.0050%, Ca: 0-0.0050%, Mg: 0 to 0.0050%, REM: 0-0.050%, Contains one or more of the following: The balance is Fe and impurities. Of the impurities O: 0.006% or less, P: 0.05% or less, S: limited to 0.0050% or less; PREN represented by the following formula 1 satisfies 28.0 to 35.0, The amount of austenite is 30% or more and 70% or less by area, The predicted sigma phase precipitation temperature T is calculated using each component distributed in the ferrite phase and is represented by the following formula 2. SIGMA is 900℃ or less 1. A duplex stainless steel forging material comprising: PREN=Cr+3.3Mo+16N...(Formula 1) T SIGMA =12Cr α +6Ni α +54Mo α +23Si α -15Mn α +465... (Formula 2) In formula 1, the element symbols indicate the content (mass%) of each element in the duplex stainless steel forging, and the element symbols with α in formula 2 indicate the content (mass%) of each element distributed in the ferrite phase in the duplex stainless steel forging.
2. Furthermore, the chemical composition, in mass%, is Al: 0.003-0.05%, Nb: 0.005-0.15%, Ti: 0.003 to 0.020%, Ta: 0.005-0.20%, Zr: 0.001 to 0.05%, Hf: 0.001-0.08%, Sn: 0.005 to 0.10%, W: 0.01-1.0%, Co: 0.01 to 1.0%, Cu: 0.01 to 3.0%, V: 0.01-0.30%, B: 0.0001 to 0.0050%, Ca: 0.0005-0.0050%, Mg: 0.0005-0.0050%, REM: 0.005-0.050%, 2. The duplex stainless steel forging material according to claim 1, further comprising one or more of the following:
3. A steel sheet having the composition according to claim 1 or 2, and a predicted sigma phase precipitation temperature T SIGMA2 3. The method for producing duplex stainless steel forgings according to claim 1, further comprising the steps of heating a steel material having a hardness of 890° C. or less to a temperature of 1150° C. to 1350° C. and then hot forging the steel material. T SIGMA2 =4Cr+28Ni+55Mo+5Si-6Mn-30N+560… (Formula 3) In the formula 3, the element symbols indicate the contents (mass%) of the respective elements in the steel material.
4. 4. The method for producing a duplex stainless steel forging according to claim 3, characterized in that in the hot forging, the final surface temperature of the hot forged duplex stainless steel material is less than 900°C.
5. A flange using the duplex stainless steel forging material according to claim 1 or 2.
6. 6. The flange of claim 5, used in food and chemical manufacturing facilities.
7. A welded structure using the duplex stainless steel forging material according to claim 1 or 2.
Citation Information
Patent Citations
Large-sized casting and forging, made of duplex stainless steel excellent in corrosion resistance and toughness, and their production
JP1997217149A
Duplex stainless steel
JP1999050199A
Two-phase stainless steel material having excellent corrosion resistance
JP2011202247A
Two-phase stainless steel and method for producing the same
JP2018193591A
Two-phase stainless steel and manufacturing method therefor
WO2018181990A1